9y+5x=11y-8x

Simple and best practice solution for 9y+5x=11y-8x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9y+5x=11y-8x equation:


Simplifying
9y + 5x = 11y + -8x

Reorder the terms:
5x + 9y = 11y + -8x

Reorder the terms:
5x + 9y = -8x + 11y

Solving
5x + 9y = -8x + 11y

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '8x' to each side of the equation.
5x + 8x + 9y = -8x + 8x + 11y

Combine like terms: 5x + 8x = 13x
13x + 9y = -8x + 8x + 11y

Combine like terms: -8x + 8x = 0
13x + 9y = 0 + 11y
13x + 9y = 11y

Add '-9y' to each side of the equation.
13x + 9y + -9y = 11y + -9y

Combine like terms: 9y + -9y = 0
13x + 0 = 11y + -9y
13x = 11y + -9y

Combine like terms: 11y + -9y = 2y
13x = 2y

Divide each side by '13'.
x = 0.1538461538y

Simplifying
x = 0.1538461538y

See similar equations:

| 6y+5=11y+30 | | (-12a)(ab)=0 | | 18x^2-72x+40=0 | | (-12abc)(4ab)=0 | | 2(x-5)=-10+2x | | 150=4x-160 | | 5*0+4y=0 | | 0=4x^2-14x+3 | | 2+5(x-8)=11-7(x-7) | | 3n+4=3n+5 | | 6x+8=10x-40 | | 2x^2+12x=-110 | | (3x-7m)(5x+3m)= | | 7+(-2)+5= | | 3a+4=3a-8 | | 2a+3b-2a-b= | | 4y+0=8 | | 27r^2+129r+84=0 | | -.1x^3+1.5x^2+80=0 | | 6p=4-9 | | 10w=60 | | 10+H=92 | | 13x-17y=-11 | | 3(4z-1)-2(z+1)=2(z+1) | | -2[4(2+2*2)]-3[5(3-4*4)]= | | (x-3)(x+4)(x+3)(x-4)=0 | | 2(4z-1)-3(z+1)=2(z+1) | | .12x^2-2x+15=0 | | 0.15*10= | | 6m-3=57 | | r(r+9)=70 | | (4x-1)(4x+1)(x-4)=0 |

Equations solver categories